KAJIAN HUKUM DAN MASYARAKAT (SEBUAH PENGANTAR) - Pudjo Utomo (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Consciously or not influenced by living together human precepts which will curb transportaion and set it between humans. Policies live together gave ancer-ancer deed whereby may run and deeds which must be avoided. Regulation of life is instructive to humans he should behave in public, and acts and force is set to ensure the discipline in society is called the rule of law.Kata kunci : Hukum, Masyarakat, Ketaatan Hukum, Psikologi Hukum.